The Visual Language of Comics: Imagery of Current Situations - วีรสาร ชญานุช (Siam Communication Review, 2019)
A current situation is an event that occurs over a period of time and impacts society. Thus, comic illustrators often rely on current situations to create a work that reflects his or her own imagination and perspective of the situation, which they share via social media. Since communicating with readers via social media is quick and easy, the author of the study chose to review visual comic language drawn during the 18-day rescue of 13 Wild Boars in the Luang Khun Nam Nang Non cave in Chiang Rai, to clearly understand the features and benefits of visual language. Visual comic language is based on the imagination of the artist using the facts which will garner public attention if published at the right moment. If this is consistent with the mood of the reader, the reader will continue to share the artist’s work on social media. Creation of comic language from current situations is clearly beneficial to artists in terms of publishing work and in terms of readers’ ability to communicate current situations.